T-Tropic Human Immunodeficiency Virus Type 1 (HIV-1)-Derived V3 Loop Peptides Directly Bind to CXCR-4 and Inhibit T-Tropic HIV-1 Infection - Sakaida, Hitoshi (American Society for Microbiology, 1998)
Certain types of chemokine receptors have been identified as coreceptors for HIV-1 infection. The process of viral entry is initiated by the interaction between an envelope protein gp120 of HIV-1, CD4, and one of the relevant coreceptors. To understand the precise mechanism of the Env-mediated fusion and entry of HIV-1, we examined whether the V3 region of gp120 of T-cell line tropic (T-tropic) virus directly interacts with the coreceptor, CXCR-4, by using five synthetic V3 peptides: two cyclized V3 peptides (V3-BH10 and V3-ELI) which correspond to the V3 regions of the T-tropic HIV-1 IIIB and HIV-1 ELI strains, respectively, a linear V3 peptide (CTR36) corresponding to that of HIV-1 IIIB strain; and cyclized V3 peptides corresponding to that of the macrophage-tropic (M-tropic) HIV-1 ADA strain (V3-ADA) or the dualtropic HIV-1 89.6 strain (V3-89.6). FACScan analysis with a CXCR-4(+) human B-cell line, JY, showed that V3-BH10, V3-ELI, and V3-89.6 but not CTR36 or V3-ADA blocked the binding of IVR7, an anti-CXCR-4 monoclonal antibody (MAb), to CXCR-4 with different magnitudes in a dose-dependent manner, while none of the V3 peptides influenced binding of an anti-CD19 MAb at all. Next, the effects of the V3 peptides on SDF-1β-induced transient increases in intracellular Ca(2+) were investigated. Three V3 peptides (V3-BH10, V3-ELI, and V3-89.6) prevented Ca(2+) mobilization. Furthermore, the three peptides inhibited infection by T-tropic HIV-1 in a dose-dependent manner as revealed by an MTT assay and a reverse transcriptase assay, while the other peptides had no effects. These results present direct evidence that the V3 loop of gp120 of T-tropic HIV-1 can interact with its coreceptor CXCR-4 independently of the V1/V2 regions of gp120 or cellular CD4.